Heterosis And Combining Ability In Forage Pearl Millet (Pennisetum Glaucum L.) Under Stress And Non-Stress Environments (Applied Biological Research, 2014)
The present investigation was undertaken for genetic analysis of forage  yield and quality traits in pearl millet (Pennisetum glaucum). A set of 15  CMS lines and 4 populations as testers were crossed in all possible  combinations to obtain 60 top cross hybrids. The hybrids were evaluated  for general combining ability (gca), specific combining ability (sca),  heterosis over two environments viz., water stress and irrigated. Analysis  of variance for quality characters revealed significant differences due to genotypes, environments and significant genotypex environment interaction  for all quality traits. The variance due to gca and sca were significant and  varied with change in the environment for all quality traits. The computed  variance ratio (σ2sca/σ2gca) revealed the predominance of non-additive  gene action in the inheritance of quality traits. The line 05111A was found best general combiner for higher quality under both the environments. Among testers, Giant bajra was best combiner for quality under both  environments. The top cross hybrids 91777A × RBC-2 and 01555A × RBC 2 were good specific combiners for high protein and fiber content. Hybrids 220A × Giant bajra, 01555A × NDFB-2 and 408A × GFB-1 exhibited high  positive significant heterosis under both the environments. The existence of  significant heterotic effect over commercial check also suggested the  presence of non-additive gene action and dominance for quality traits.
Keywords: Combining ability; environments; forage; heterosis; hybrids; pearl millet; quality